The liverwort oil body is formed by redirection of the secretory pathway - Kanazawa, Takehiko (Nat Commun, 2020)
Eukaryotic cells acquired novel organelles during evolution through mechanisms that remain largely obscure. The existence of the unique oil body compartment is a synapomorphy of liverworts that represents lineage-specific acquisition of this organelle during evolution, although its origin, biogenesis, and physiological function are yet unknown. We find that two paralogous syntaxin-1 homologs in the liverwort Marchantia polymorpha are distinctly targeted to forming cell plates and the oil body, suggesting that these structures share some developmental similarity. Oil body formation is regulated by an ERF/AP2-type transcription factor and loss of the oil body increases M. polymorpha herbivory. These findings highlight a common strategy for the acquisition of organelles with distinct functions in plants, via periodical redirection of the secretory pathway depending on cellular phase transition.